2012
DOI: 10.4172/2155-6199.1000139
|View full text |Cite
|
Sign up to set email alerts
|

Augmenting Composting Microbial Community with Thermophilic Cellulolytic Organisms for Enhanced Degradation of Phenolic Compounds in Creosote Treated Wood Waste

Abstract: Creosote is widely used as a wood preservative in railway sleepers, utility poles, bridges, building foundations, fences, stakes for vegetables and fruits, garden furniture and outdoor recreational facilities. Contamination of soil and water and threat to human and animals health are the major constraints to disposal of creosote-treated wood waste. Composting provides a treatment option for creosote-treated wood waste and production of a valueadded product. The aim of this study was to test the effectiveness o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…It is known that water is the medium for nutrient transportation and metabolic reactions in microorganisms. Nutrient availability is affected by the water content in the microenvironment of the microbes, especially in the thin liquid layers on particle surfaces (Ghaly, Dave, & Zhang, ). However, no significant correlation between moisture and fungal community composition was obtained in this research, indicating that bacterial communities may be more sensitive to fluctuations in moisture content than fungal communities.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that water is the medium for nutrient transportation and metabolic reactions in microorganisms. Nutrient availability is affected by the water content in the microenvironment of the microbes, especially in the thin liquid layers on particle surfaces (Ghaly, Dave, & Zhang, ). However, no significant correlation between moisture and fungal community composition was obtained in this research, indicating that bacterial communities may be more sensitive to fluctuations in moisture content than fungal communities.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the source of the wood chips, they may contain toxic chemicals, which pollute soil and ground water. It has been found that some of the recycled waste wood used for making landscape mulch products is contaminated with various chemicals, such as creosote, chromium copper arsenate or lead-based paints used for wood preservation against fungi and insects [83][84][85].…”
Section: Toxicity Of Mulches In Green Areasmentioning
confidence: 99%